If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 4 = 6b + -4 Reorder the terms: 4 + 2b = 6b + -4 Reorder the terms: 4 + 2b = -4 + 6b Solving 4 + 2b = -4 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 4 + 2b + -6b = -4 + 6b + -6b Combine like terms: 2b + -6b = -4b 4 + -4b = -4 + 6b + -6b Combine like terms: 6b + -6b = 0 4 + -4b = -4 + 0 4 + -4b = -4 Add '-4' to each side of the equation. 4 + -4 + -4b = -4 + -4 Combine like terms: 4 + -4 = 0 0 + -4b = -4 + -4 -4b = -4 + -4 Combine like terms: -4 + -4 = -8 -4b = -8 Divide each side by '-4'. b = 2 Simplifying b = 2
| 2x^2+19x-7.5=0 | | (3x^(2/3))+(10x^(1/3))=8 | | 17=-13+x | | 8/15x=8-2/15 | | 19T-(-25)=158 | | 7b-3b=36 | | 16x-9=4(4x+7) | | 3/x=(9/8x)+3 | | 4x-3=6y+8 | | 15=K/5+23 | | 52=6N-2 | | 7N-22=13 | | 6+2+3+20=x | | (x+5)(x+3)=(x+1)(x+7)+10 | | 3(8)-3x=18 | | 40+4j=2(-4-13j) | | 64=d/-8+69 | | 3x-25=x+35 | | 6n+8=5 | | xy-y=a+d | | 5x+15x-7=5(4x+4) | | (3x-2)(x+3)=-6x-4 | | (x+5)(x-5)=(x+1)(x+7)+10 | | 3(x-9)+8=62 | | 2x*7=10 | | (4a+5b)(8a-7b)= | | 260=-v+165 | | 73.543-23.683= | | (2x-1)/4=(x+5)/3 | | 2a+3=(1)/(2)(6+4a) | | 7X=7.5 | | 13x+1=13x+59 |